Implementasi Prinsip Ekonomi Gerakan Untuk Pengaturan Tata Letak Fasilitas Kerja Pada Pemrosesan Batu Alam - Luciana Triani Dewi; Marta Hayu Raras Sita Rukmika Sari; Chandra Dewi; Vincensius Ariyono (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2015)
The layout and arrangement of production facilities is one key to productive and efficient working environment. In planning and setting the layout of the factory, one of the basic principles that should be considered is the planning of work stations. Every operation must be designed in detail by applying economic principles in the movement of goods to and from work station. The study was conducted in a small industry which manufactures natural stone craft in Yogyakarta. Development of work stations design remains to reduce unnecessary activities such as searching and moving equipment activity. Economic principles applied in the development of a facility layout. Evaluation of the layout design was used time study analysis based on the two hand chart before and after improvement of work station layout. Implementation of improved design showed improvement working time for the process which increasing efficiency up to 31.51%. Reduction standard time is achieved because the work methods becomes easier and faster than before.